Soğuk Savaş Döneminde Türk Dış Politikasının Kimliği: İdeolojinin Sonu mu? - Fulya ÖZKAN (Gazi Akademik Bakış)
In the first half of the article, social movements which were shaped by a variety of ideological identities will be analyzed. Then, the article will evaluate the end of the ideology thesis which became popular in the 1960s. This theory suggests that different ideological perspectives developed a common economic policy. In the second half, the article will focus on Turkey as a case study and examine to what extent ideologies like nationalism, Islamism and Westernism had an impact on Turkish foreign policy. The article will argue that different identities shared a similar viewpoint not in economics but when the foreign interests of the state were at stake. The article will make an evaluation of this difference and suggest that Cold War politics played a role because especially following the Second World War, different political ideologies started following a similar trend in their foreign policy visions. The article will underline that this picture contradicts with the expectations of the end of the ideology thesis for the contemporary underdeveloped countries. This analysis will present a pluralist perspective which may allow to evaluate Turkish foreign policy making process through both realist, liberal and constructivist perspectives.